Heat loss from hot water flowing in a copper pipe insulated using air enclosed with a PVC pipe - Albayani, A.; Mirmanto, M.; Syahrul, S. (Universitas Mataram, 2018)
This paper presents investigations of heat loss from hot water flowing in an insulated copper pipe. Investigations were performed to know the heat loss from a copper pipe insulated using air enclosed with a PVC pipe. The fluid temperature used was kept at approximately 75°C in the entrance and its mass flow rate was around 12 g/s. The nominal copper pipe diameter was 6.35 mm; while the diameters of the PVC pipe were ranging from 12.7 mm to 5.08 mm. The length of the test section was approximately 3000 mm. The results show that the biggest heat loss is found using the bare copper pipe. When the copper pipe is insulated using air enclosed with a PVC pipe, the heat loss decreases with the increased PVC pipe diameters. The trend of the heat loss agrees with the critical insulation diameter theory.